Microbial Imaging - Savidge, Tor; Ed. Pothoulakis, Charalabos; Ed (academic Press, 2005)
Recent advances in molecular technology have provided new microbial imaging tools, not only complementing more classical methods, but in many cases significantly enhancing the sensitivity and efficiency in which studies may be conducted. These technologies are applicable to a wide range of problems in contemporary microbiology, including strain selection, understanding microbial structure, function and pathophysiology, as well as in the development of anti-microbial agents and vaccines. This volume emphasizes detailed methodology, provides a theoretical background and lists potential applicat.